The Effect of Steeping Water Temperature Of Cinnamon (Cinnamomum Burmannii) and Steeping Time With Test Time on the Glycemic Response of Diabetic Rats - Tarigan, Ariko Targinta; Lubis, Zulkifli; Siagian, Albiner (Asian Journal of Pharmaceutical Research and Development, 2023)
Diabetes Mellitus (DM) is a disease in which the body is unable to metabolize fats, proteins and carbohydrates which is characterized by high blood glucose levels or commonly known as hyperglycemia. Until 2019, 10.9 million DM cases were found in Indonesia and are suspected of continuing to increase. Cinnamon (Cinnamomum Burmannii) has several active ingredients vizcoumarin, cinnamat, cinnamaldehid, polyphenols and flavonoid can increase glucose transport by GLUT 4 in adipose cells and skeletal muscles so as to significantly reduce blood glucose. Thus, cinnamon has the potential to be a useful product for the community, namely a diabetes herbal medicine. The purpose of this research was to determine the ratio of the temperature of the cinnamon steeping water with the duration of steeping on the glycemic response of diabetic rats. This research uses Completely randomized design (CRD) with 2 factors, namely the first factor (P): steeping water temperature (65 oC, 75 oC, and 85 oC) and brewing time (20 minutes, 25 minutes and 30 minutes) and the second factor (L): test time (30 minutes, 60 minutes, 90 minutes and 120 minutes). This study also carried out control (-) and control (+) as a preliminary study to determine the glycemic response in test animals. Each treatment will be repeated 3 times to obtain 33 experimental units. The parameters analyzed were blood sugar levels, the percentage (%) increase in blood sugar levels, and the percentage (%) decrease in blood sugar levels. The results showed that temperature of the cinnamon steeping water (Cinnamomum Burmannii) and the duration of brewing can reduce the blood sugar levels of mice every time the test is carried out. The best treatment was obtained from the ratio of the temperature of the steeping water and the duration of steeping, namely 65 oC and brewing time for 25 minutes, determined based on the percentage decrease in blood sugar level, which is equal to 53,02%.